Clostridium difficile in Clinical Practice: Increasing Rates, More Virulent Organisms and New Therapies on the Horizon - Thomas J Louie (Canadian Journal of Infectious Diseases and Medical Microbiology)
Clostridium difficile-associated diarrhea has recently come under increasing scrutiny because of outbreaks of disease in eastern Canada in association with a hypervirulent ribotype 027 (NAP1) strain. Hospitals in the United States, the United Kingdom and Europe have been affected as well. Epidemiological studies are underway to determine the presence of the more virulent strain of C difficile in hospitals across Canada. Because this strain is highly quinolone resistant, it is suspected that overuse of that class of antimicrobial agent may be a selection factor for this strain. Although C difficile-associated diarrhea is usually considered a nosocomial infection, approximately one-quarter of cases occur in the community. Recurrence following successful resolution of diarrhea occurs in one in five patients treated with metronidazole or vancomycin; relapse is more common in patients needing retreatment. New therapies that may have equivalent or higher response rates and lower recurrence rates are being investigated. It is hoped that these new treatments will be a substantial improvement over current therapies. In the interim, prudent antimicrobial use and attention to infection control practices are the main preventive strategies. Prompt testing for C difficile toxin in patients with diarrhea after antibiotic exposure, discontinuation of unnecessary antibiotic therapy and rapid initiation of treatment should minimize complications. With the appearance of more toxigenic strains of C difficile, careful monitoring of patients to detect suboptimal clinical response is necessary.